Los negros ingleses o creóles de Honduras: etnohistoria, racismo, y discursos nacionalistas excluyentes en Honduras. - Amaya, Jorge Alberto (Sociedad y Economía, 2007)
This essay analyses the ethnohistory of the black english people who live in the caribbeancost of Honduras, taking as a clue the emigration waves that occurred in the last centuries. Theessay also discusses some racist manifestations against the presence of these people by asegment of the honduran intelligentsia that was trying to consolídate national imaginaries inwhich Honduras is seen as a "mestizo nation".